Trends and challenges of indonesian social entrepreneurship research: a systematic literature review (2013-2023) - Natalia Sari Pujiastuti; Bulan Prabawani; Ari Pradhanawati; Sari Listyorini (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
The rapid expansion of social enterprises in Indonesia reflects a growing response to pressing socio-economic challenges. Existing research on Indonesian social entrepreneurship often examines these issues in isolation, lacking a comprehensive, integrative perspective. This study addresses this gap by conducting a Systematic Literature Review (SLR) of 94 Scopus- and Google Scholar-indexed research articles, analyzed using Publish or Perish 8 and Covidence software. The findings reveal six interdependent dimensions shaping Indonesia’s social entrepreneurship ecosystem: (1) organizational and policy frameworks, (2) business models and financial sustainability, (3) social and economic impact, (4) education and innovation, (5) religiosity and cultural influences, and (6) gender dynamics. Unlike prior studies that focus predominantly on descriptive narratives and case studies, this research provides a holistic, critical analysis, highlighting persistent gaps in policy implementation, financial accessibility, and cross-sector collaboration. The study also situates Indonesia’s social entrepreneurship landscape within a broader global context, identifying key disparities and potential areas for alignment with international best practices. The findings carry significant implications: for academics, the study establishes a foundation for future research on policy interventions and sustainable business models; for policymakers, it underscores the urgency of developing structured financial support mechanisms and regulatory frameworks; and for social entrepreneurs, it provides a strategic roadmap to navigate challenges, leverage opportunities, and enhance impact. Ultimately, this research underscores the critical need for targeted interventions to strengthen Indonesia’s social enterprise sector. Without a concerted effort to address systemic constraints, the sector risks stagnation, limiting its ability to drive inclusive economic growth and social transformation.